Rearranged Sesquiterpenes and Branched Polyketides Produced by the Endophyte Camarops sp. - Gubiani, Juliana R. [UNESP]; Nogueira, Claudio R.; Pereira, Marcos D. P. [UNESP]; Young, Maria C. M.; Ferreira, Paulo M. P.; Moraes, Manoel O. de; Pessoa, Claudia; Bolzani, Vanderlan S. [UNESP]; Araujo, Angela R. [UNESP] (Elsevier B.V., 2016)
Two rearranged sesquiterpenes, 3,5,9-trihydroxy presilphiperfolane (1) and 4-deoxy-10-oxodihydrobotrydial (2), and two branched polyketides, 4-((E)-pent-1-enyl)-3-((1'S,2'S)-1',2'-dihydroxybut-3-enyl)5H- furan-2-one (3) and (2E,4R)-2,4-dimethylnon-2-enoic acid (4), along with three known compounds (2E,4S)-2,4-dimethyloct-2-enoicacid (5), xylarenone C (6), xylarenone D (7), were isolated from solid substrate cultures of Camarops sp., an endophyte of Alibertia macrophylla (Rubiaceae). The structures were established by means of NMR and HRESIMS analyses. The absolute stereochemistry of 3 was determined through the application of the modified Mosher method. Compounds 6 and 7 exhibited cytotoxic activity against leukemia (HL-60), melanoma (MDA/MB-435), colon (HCT-8) and glioblastoma (SF-295) human tumor lines, while compounds 4-7 presented acetylcholinesterase inhibition. (C) 2016 Phytochemical Society of Europe. Published by Elsevier Ltd. All rights reserved.
Keywords: Rearranged sesquiterpenes; Branched polyketides; Endophytic fungus; Camarops sp.; Alibertia macrophylla